Slower lower limb blood pooling in young women with orthostatic intolerance. Issue 1 (27th November 2014) - Lindenberger, Marcus; Länne, Toste
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Orthostatic stress is mostly caused by venous blood pooling in the lower limbs. Venous distension elicits sympathetic responses, and increased distension speed enhances the cardiovascular response. We examine whether lower limb blood pooling rate during lower body negative pressure is linked to orthostatic intolerance. What is the main finding and its importance? A similar amount of blood was pooled in the lower limb, but at a slower rate in women who developed signs of orthostatic intolerance. The difference in blood pooling rate increased with orthostatic stress and was most prominent at a presyncope‐inducing level of lower body negative pressure. The findings have implications for the pathophysiology as well as treatment of orthostatic intolerance. Vasovagal syncope is common in young women, but its aetiology remains elusive. Orthostatic stress‐induced lower limb blood pooling is linked with central hypovolaemia and baroreceptor unloading. Venous distension in the arm elicits a sympathetic response, which is enhanced with more rapid distension. Our aim was to study both the amount and the speed of lower limb pooling during orthostatic stress and its effects on compensatory mechanisms to maintain cardiovascular homeostasis in women with orthostatic intolerance. Twenty‐seven healthy women, aged 20–27 years, were subjected to a lower body negative pressure (LBNP) of 11–44 mmHg. Five women developed symptoms of vasovagal syncope (orthostatic intolerant) and were compared with the remaining women, who tolerated LBNP well (orthostatic tolerant). Lower limb blood pooling, blood flow and compensatory mobilization of venous capacitance blood were measured. Lower body negative pressure induced equal lower limb blood pooling in both groups, but at a slower rate in orthostatic intolerant women (e.g. time to 50% of total blood pooling, orthostatic intolerant 44 ± 7 s and orthostatic tolerant 26 ± 2 s; P < 0.001). At presyncope‐inducing LBNP, the mobilization of venous capacitance blood was both reduced (P < 0.05) and much slower in orthostatic intolerant women (P = 0.0007). Orthostatic intolerant women elicited blunted arterial vasoconstriction at low‐grade LBNP, activating only cardiopulmonary baroreceptors, while orthostatic tolerant women responded with apparent vasoconstriction (P < 0.0001). In conclusion, slower lower limb blood pooling could contribute to orthostatic intolerance in women. Mobilization of venous capacitance blood from the peripheral to the central circulation was both slower and decreased; furthermore, reduced cardiopulmonary baroreceptor sensitivity was found in women who developed orthostatic intolerance. Further studies including women who experience syncope in daily life are needed.